Kawaii In Taiwan Politics - Yin , C. Chuang (Penerbit Universiti Sains Malaysia (USM Press), 2011)
By investigating the case of A-Bian Doll (扁娃, see Figure 1), this paper explores how Kawaii (可愛い, the Japanese word for "cute") has pervaded in Taiwan, and has since been appropriated by Taiwanese politicians as one of the significant methods for advancing democratisation, and constructing collective imagination and national identities. Particularly, this paper explores how Kawaii is represented and reproduced in Taiwan politics. I will first discuss how Kawaii is produced and consumed in Taiwanese people's everyday life in relation to the process of democratisation and the formation of consumer society. I will then move to the discussion of the A-Bian Doll and its accessories, which is arguably the most significant example of how Kawaii is made tangible in Taiwanese politics. I will examine how Kawaii is appropriated as a familiar element from Taiwanese culture by former President Chen's staffers, and is then injected into ingredients drawn from Taiwanese baseball culture and the features of Chen to produce the A-Bian Doll and its accessories. By making and advertising the A-Bian Doll and its accessories, Chen's staffers create a new culture, and then feed this back into social circulation, mobilise supporters and gain votes.